A Novel Type I Interferon-producing Cell Subset in Murine Lupus - Lee, Pui Y. (2008)
Excess type-I interferons (IFN-I) have been linked to the pathogenesis of systemic lupus erythematosus (SLE). Therapeutic use of IFN-I can trigger the onset of SLE and most lupus patients display upregulation of a group of interferon stimulated genes (ISGs). While this “interferon signature” has been linked with disease activity, kidney involvement, and autoantibody production, the source of IFN-I production in SLE remains unclear. Tetramethylpentadecane (TMPD)-induced lupus is at present the only model of SLE associated with excess IFN-I production and ISG expression. Here we demonstrate that TMPD treatment induces an accumulation of immature Ly6C(hi) monocytes, which are a major source of IFN-I in this lupus model. Importantly, they were distinct from interferon-producing dendritic cells. The expression of IFN-I and ISGs was rapidly abolished by monocyte depletion whereas systemic ablation of dendritic cells (DCs) had little effect. In addition, there was a striking correlation between the numbers of Ly6C(hi) monocytes and the production of lupus autoantibodies. Therefore, immature monocytes rather than DCs appear to be the primary source of IFN-I in this model of IFN-I dependent lupus.